Rare RELN variants affect Reelin–DAB1 signal transduction in autism spectrum disorder. Issue 10 (26th July 2018) - Sánchez‐Sánchez, Sandra M.; Magdalon, Juliana; Griesi‐Oliveira, Karina; Yamamoto, Guilherme L.; Santacruz‐Perez, Carolina; Fogo, Mariana; Passos‐Bueno, Maria Rita; Sertié, Andrea L.
Abstract: The Reelin–DAB1 signaling pathway plays a crucial role in regulating neuronal migration and synapse function. Although many rare heterozygous variants in the Reelin gene ( RELN ) have been identified in patients with autism spectrum disorder (ASD), most variants are still of unknown clinical significance. Also, genetic data suggest that heterozygous variants in RELN alone appear to be insufficient to cause ASD. Here, we describe the identification and functional characterization of rare compound heterozygous missense variants in RELN in a patient with ASD in whom we have previously reported hyperfunctional mTORC1 signaling of yet unknown etiology. Using iPSC‐derived neural progenitor cells (NPCs) from this patient, we provide experimental evidence that the identified variants are deleterious and lead to diminished Reelin secretion and impaired Reelin–DAB1 signal transduction. Also, our results suggest that mTORC1 pathway overactivation may function as a second hit event contributing to downregulation of the Reelin–DAB1 cascade in patient‐derived NPCs, and that inhibition of mTORC1 by rapamycin attenuates Reelin–DAB1 signaling impairment. Taken together, our findings point to an abnormal interplay between Reelin–DAB1 and mTORC1 networks in nonsyndromic ASD. Abstract : Although increasing evidence suggests that Reelin‐DAB1 signaling dysfunction may confer risk to autism spectrum disorder (ASD), few studies to date have directly demonstrated impairment of the Reelin signal transduction cascade in ASD patients. Here, we describe diminished Reelin secretion and defective Reelin‐DAB1 signaling in neural progenitor cells (NPCs) derived from iPSCs of an ASD patient (F2688) carrying rare compound heterozygous missense variants in RELN . Also, our results suggest an abnormal interplay between Reelin‐DAB1 and mTORC1 signaling pathways in patient‐derived NPCs.